A Systematic Literature Review on Agricultural Effluent Treatment using Advanced Membrane Technologies - Tutuk Djoko Kusworo; Dani Puji Utomo (Diponegoro University, 2025)
Agricultural wastewater poses significant environmental challenges due to its complex composition, including high concentrations of nutrients, organic matter, and emerging contaminants. Membrane-based technologies have emerged as advanced solutions for effective treatment and resource recovery from such effluents. This review provides a comparative analysis of various membrane systems—pressure-driven membranes, membrane bioreactors (MBRs), photocatalytic membranes, forward osmosis (FO), membrane distillation (MD), and adsorptive membranes—focusing on their performance in terms of pollutant removal, fouling behavior, energy consumption, and cost-effectiveness. Photocatalytic and FO membranes exhibit high potential for removing persistent organic pollutants and ensuring water reuse, while MD and MBRs demonstrate robust performance in nutrient and organic load reduction. Adsorptive membranes offer selective removal capabilities, particularly for antibiotics and pesticides, although scalability remains a concern. Advances in membrane materials, surface modifications, and hybrid system integration are paving the way for enhanced operational efficiency. The findings underscore the need for integrated, multi-barrier treatment approaches and continued innovation to meet the sustainability requirements of agricultural wastewater management..